The Houses of Scholars in Tlemcen Zayani and their Civilizational Contributions: The House of Bani Marzouk as a Model - Hakim ali abbass; salah herouini (Social Empowerment Journal, 2023)
scientific movement, which contributed to making it a center for cultural radiation, due to the interest of its authorities in this aspect and the emergence of several scientific families that contributed their cultural and scientific production to the cultural structure. The family of Bani Marzouk is among the most prominent of these scientific houses that have recorded their presence in the intellectual production of their sons in most aspects of knowledge and science.      Therefore, this intervention to monitor the scientific houses in Tlemcen during the Zayani era was limited to a model embodied in the House of Marzouki, which actively contributed to promoting the growth of the cultural movement, making it a shelter for scholars from all sides and a center of civilization during successive periods of time.